First record of two potentially toxic dinoflagellates in tide pools along the Sardinian coast. Issue 1 (2nd January 2017) - Calabretti, C.; Citterio, S.; Delaria, M.A.; Gentili, R.; Montagnani, C.; Navone, A.; Caronni, S.
Abstract: Nowadays harmful algal blooms (HABs) represent a serious problem for the conservation of the biodiversity in the Mediterranean Sea. Nevertheless the knowledge on the presence of potentially toxic benthic microalgae in particular habitats, such as tide pools, is still scarce. In order to detect HAB-producing benthic microalgae in tide pools of the rocky intertidal zone, a pilot study was conducted in Tavolara Punta Coda Cavallo Marine Protected Area (MPA) during the late spring of 2016. Three different pools were sampled in two study sites (six pools were sampled in total) and the cell density of toxic species was estimated in each. In all the collected samples, the two potentially toxic dinoflagellates, Prorocentrum lima (Ehrenberg) F. Stein and Coolia monotis Meunier, were recorded and significant differences in their density were observed, in relation to both sites and pools.